Students’ Cognitive Ability in View of the Personality Type of Hippocrates Galenus - Nur Hasanah Rodia Harahap; Eliza Putriansyah; Adelina Rodia Simanullang; Yolanda Yolanda (Edumaspul: Jurnal Pendidikan, 2023)
The personality type proposed by Hippocrates and Galenus has become a topic of discussion in the world of education. While it cannot be considered an accurate and valid measure of a student's cognitive ability, understanding personality type can help teachers or parents understand student learning styles and support learning more effectively and efficiently. Each student has a learning style that is different from one another. and understanding personality types can help identify student strengths and weaknesses and provide learning methods that fit student learning styles. This article discusses the personality types of Hippocrates and Galenus and their influence on students' cognitive abilities. This article also suggests that understanding personality type is only one of the factors that influence students' cognitive abilities, and effective learning strategies must consider other factors such as students' interests and motivation, learning objectives, and learning contexts. This article recommends several references about student personality types and cognitive abilities that can be used as teaching materials for teachers or parents.